ANALYSIS OF USING INSTAGRAM AS A MEANS OF HIGHWAY INFORMATION ON Idul Fitri 2022 - Muhammad Kevin Arnanda Imron; K,Y,S Putri (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
Instagram is a new media that is advancing very rapidly, in Instagram, there are many users or perpetrators of citizen journalism, to find out whether @jktinfo has used Instagram's features as well as possible and to find out if @jktinfo is included in the new respected media. The method used in this research is descriptive qualitative which is done through observation and documentation from @jktinfo. The @jktinfo account has fulfilled the features and is also interactive several times to create a two-way communication where @jktinfo provides information related to citizen journalism, according to McQuaill's theory it can be said that @jktinfo is an account that is good in management and leads to something higher.